2003
DOI: 10.1177/096914130301000306
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Result and Reattendance in the Ontario Breast Screening Program

Abstract: Objective: To determine the association between initial screen result and returning for a second screen in an organised breast screening programme for women with a biennial screening recommendation. Setting: Women who attended the Ontario Breast Screening Program (OBSP).Methods: A retrospective cohort study was conducted of 140,723 Ontario women aged 50 years ond older who had an initial screen at the OBSP between 1 July 1990 and 31 December 1995 and were followed until 30 June 1998. Rescreening rates at 36 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Other U.S. studies have shown that false-positives either had no effect on 3133 or seemed to facilitate subsequent mammography use. 7,8 Our findings are more consistent with two Canadian 16,17 and several European studies 1115 showing that false-positive results interfere with subsequent screening. Given controversy concerning the benefits and potential harms of mammography screening, 20 monitoring the effects of false-positive test results and whether physicians advise women to be screened should remain a public health priority.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other U.S. studies have shown that false-positives either had no effect on 3133 or seemed to facilitate subsequent mammography use. 7,8 Our findings are more consistent with two Canadian 16,17 and several European studies 1115 showing that false-positive results interfere with subsequent screening. Given controversy concerning the benefits and potential harms of mammography screening, 20 monitoring the effects of false-positive test results and whether physicians advise women to be screened should remain a public health priority.…”
Section: Discussionsupporting
confidence: 90%
“…1115 Canadian studies also suggest a negative effect of false-positives on subsequent mammography screening. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Several other studies from Europe and Canada found no difference in re-screening (1316,27), and yet others have reported lower re-screening rates among FPs than among TNs (1820,2830). These inconsistent results suggest both secular and geographic variation in the impact of FP mammography on adherence to screening recommendations among the USA, Europe and Canada (21).…”
Section: Discussionmentioning
confidence: 86%
“…Several studies in the UK and Canada have shown that women undergoing false-positive mammography were less likely to return for a subsequent screening appointment. 1,7-9 However a systematic review of 23 studies found that US women who received a false-positive result were more likely to return for routine screening than those who received a normal result; 2 there was no difference among European women, and among Canadian women those with a false-positive assessment were less likely to return for screening.…”
Section: Discussionmentioning
confidence: 99%